The Effectiveness of Canva Application as a Media in Writing Greeting Card at the Eight Grade of SMP Negeri 12 Banjarmasin - Maulida Noor; Elanneri Karani; Ristati Ristati (Journal on Education, 2023)
The use of technology for education is good to support the teacher in transferring knowledge that they want to teach for the students to improve their skill or knowledge. One of the digital educational apps that can help in writing is Canva. According to Christiana & Anwar (2021) canva is a website graphic design tool, a drag-and drop format of visual technology media, provides access to more than one million photos, graphics and fonts. This study aims to find the effect of using canva as a media in writing greeting card at the eight grade of SMP Negeri 12 Banjarmasin. The research subject was the eight grade students of SMP Negeri 12 Banjarmasin. This research is classified as a true experimental design. The population of this research is 59 students but only 48 students are choosen as the sample based on 5% mistake level. This study is a quantitative method that using Randomized-Groups Pre-test-Post-Test Control Group Design. The instrument that used was writing greeting card. The data were collected in several steps: pre-test, treatment, and post-test; the data were processed in several steps: collecting data, scoring and calculating; data analysis was conducted using SPSS application including test of data normality, homogeneity and tests of Hypothesis. The result of this study conclude that the use of canva as a media has significant effect for the students in writing greeting card.